Compulsory kindergarten education and early-teenage literacy in the Philippines - Michael Ralph M. Abrigo; Kris A. Francisco (Asian Development Bank Institute (ADBI), 2023)
We assessed the impact of compulsory kindergarten education on early-teenage basic and functional literacy skills achievement using a large-scale natural experiment in the Philippines. In 2012, the Philippine government mandated compulsory kindergarten attendance for children aged five years or older prior to enrolling in the country's basic education cycle. This created a nontrivial discontinuity in the propensity of kindergarten school attendance among different cohorts of children, which we exploited in this study. We find that children who were exposed to the policy were no more likely to be able to read, write, and calculate by the age of 11 to 13 years than comparable peers who were not compelled to attend kindergarten. However, those who were exposed to the policy were more likely to reach full functional literacy by early teenage, which is likely due to dynamic complementarities in the formation of skills. While other children were able to eventually catch up with basic literacy skills in later childhood, children who attended kindergarten were more likely to be able to read and write before entering primary school, which allowed them to develop further skills later.
Keywords: D83; I21; I28; 330; early-childhood education; literacy